Edna St. Vincent Millay - Millay, Edna St. Vincent, 1892-1950 (New York : Sterling Pub. Co., 1999)
A selection of thirty-four poems from the Pulitzer Prize winner, including an introduction about her life and work
Includes index
Keywords: Children's poetry, American; Poets, American -- Maine; American poetry